Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content:1. The reality of teaching strategies used by Arabic language teachers in primary stage to develop their students’ self-learning skillsCo-Prof. Nawaf Saleh Al-Sulami, Ms. Amal Nasser Al-Harbi2. The effects of teaching a book unit that contains controversial scholars’ opinions on the critical thinking of high school studentsMr. Majdi Ahmed Hammad Aljohani, Dr. Mohammed Saad Alqarni3. Obstacles to using learning platforms during the COVID-19 pandemic from the point of view  of primary school teachers in RiyadhMs. Noura Ghazi Al-Shaibani, Prof. Ahmed Mohammed Al-Hussein4. Teachers’ practice of mathematical representation, and its relationship to the preschooler’s utilization of it in expressing mathematical ideasMrs. Reem Khlifa Al-Owaidh, Co-Prof. Sama Fouad Khomais5. The degree of inclusion of higher-order thinking skills in the mathematics textbook for the first year of secondary school in Kingdom of Saudi ArabiaMrs. Amal Ali Muhammad Al-Shehri
Keywords: Journal of Curriculum and Teaching Methodology